Human CD26high T cells elicit tumor immunity against multiple malignancies via enhanced migration and persistence. Issue 1 (December 2017) - Bailey, Stefanie; Nelson, Michelle; Majchrzak, Kinga; Bowers, Jacob; Wyatt, Megan; Smith, Aubrey; Neal, Lillian; Shirai, Keisuke; Carpenito, Carmine; June, Carl; Zilliox, Michael; Paulos, Chrystal
Abstract CD8+ T lymphocytes mediate potent immune responses against tumor, but the role of human CD4+ T cell subsets in cancer immunotherapy remains ill-defined. Herein, we exhibit that CD26 identifies three T helper subsets with distinct immunological properties in both healthy individuals and cancer patients. Although CD26neg T cells possess a regulatory phenotype, CD26int T cells are mainly naive and CD26high T cells appear terminally differentiated and exhausted. Paradoxically, CD26high T cells persist in and regress multiple solid tumors following adoptive cell transfer. Further analysis revealed that CD26high cells have a rich chemokine receptor profile (including CCR2 and CCR5), profound cytotoxicity (Granzyme B and CD107A), resistance to apoptosis (c-KIT and Bcl2), and enhanced stemness (β-catenin and Lef1). These properties license CD26high T cells with a natural capacity to traffic to, regress and survive in solid tumors. Collectively, these findings identify CD4+ T cell subsets with properties critical for improving cancer immunotherapy. The role of human CD4+ T cell subsets in cancer immunotherapy is still unclear. Here, the authors show that CD26 identifies three CD4+ T cell subsets with distinct immunological properties in both healthy individuals and cancer patients.